UPAYA UNESCO DALAM MERESPONS PERUSAKAN SITUS WARISAN BUDAYA DI UKRAINA TAHUN 2022-2025 - Nabilla, Dhiva Zayyana Syifa'un; Arie, Ferdinand; Wulandari, Yaasiinta Fajar; Islamiyah, Selvi Nur Islamiyah; Siahaya, James Arthur; Hapsari, Renitha Dwi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Armed conflict not only threatens human lives, but also damages infrastructure and cultural heritage as the collective identity of a nation. Russia's invasion of Ukraine has caused damage to hundreds of cultural sites of historical, religious, and social value. As the UN agency responsible for protecting cultural heritage, UNESCO is taking action to prevent further damage, document affected sites, and rally international support for restoration efforts. This study aims to analyse how UNESCO responded to the destruction of cultural sites in Ukraine between 2022 and 2025. The theoretical framework used is cultural heritage to understand the importance of protecting cultural heritage, as well as the theory of international organisation implementation (Joachim et al., 2007) to explain the concrete efforts made in the context of armed conflict. The method used is descriptive qualitative with literature review. The research results show that UNESCO uses two approaches, namely normative (authority and legitimacy) and management (monitoring, capacity building, and problem solving). Normatively, UNESCO establishes the status of World Heritage in Danger, Enhanced Protection, and Blue Shield marking to strengthen awareness and the international legal basis. From a management perspective, UNESCO conducts monitoring in collaboration with UNITAR UNOSAT and the Executive Board, implements capacity building with ICCROM, the Getty Conservation Institute, HEART, and the Smithsonian SCRI, and carries out problem-solving through ICCROM FAR workshops, the Maidan Museum, HERI, UNESCO/ICOMOS expert missions, and international conferences. These efforts have resulted in risk assessments, digital documentation, and medium- and long-term recovery action plans. Both approaches underscore that UNESCO is not only establishing symbolic norms but also implementing concrete technical actions to ensure the sustainability of cultural heritage amid conflict.